Improving Efficiency and Standards of the Academic Libraries According to Educational Innovations - Lasić-Lazić, Jadranka; Afrić, Vjekoslav; Banek Zorica, Mihaela; Divjak, Blaženka (2004)
It is beyond dispute that today any relevant mention of education and educational reforms automatically includes the concept of lifelong learning. Due to various changes we have to get a brand new perspective on the situation in education, business, and management. This innovative learning environment changes and redefines the role both of the library and the librarian in the context of educational system. Analysing the organization and the activities of the libraries at the Fac-ulty of Philosophy, University of Zagreb the authors of the paper try to establish how well the academic libraries and librarians in Croatia can support recent changes in education and what efforts are being made for the improvement of their efficiency and general standards. Primarily the authors will indicate that pro-viding some extra space for the libraries and ensuring adequate training for the librarians can strongly stimulate the improvement in the efficiency and quality of the libraries so they would conform to the con-temporary educational innovations.
Projekt MZOS
ENG